Job Satisfaction Mediates the Effect of Work Environment and Competence on Performance - Gerrit M. Pentury; Paul Usmany (International Journal of Social Science and Business, 2023)
This study aims to analyze the influence of the work environment and competence on the performance of education personnel at the Pattimura University Rectorate Office, as well as examine the mediating role of job satisfaction in the relationship between the work environment and competence on performance. The type of research used is explanatory research. The unit of analysis is the education staff of the Rector of Pattimura University. Data collection was carried out by questionnaire, with the number of respondents as many as 57 education personnel from a total population of 130 education personnel. Data collection techniques were interviewed using questionnaire models and observation techniques. The questionnaire contains 34 question items. To test the effect a path analysis tool was used using the SPSS program version 26. The results showed that the work environment affects job satisfaction; In addition, competence affects job satisfaction; These findings suggest that the work environment affects performance. Competence affects performance; Job satisfaction affects performance; Job satisfaction as a mediating variable reinforces the influence of the work environment on performance; Job satisfaction as a mediating variable reinforces the influence of competence on performance. Work environment, competence, and job satisfaction as mediating variables with a coefficient of determination of 79.1% and the remaining 20.9% are explained by other variables outside the model. The results of the path analysis can be concluded that the indirect influence of competence through job satisfaction is an effective path to improve performance. This research has important implications for organizational managers, especially in terms of human resource development and performance improvement.